Bioelectrochemical Composites: Living Bioelectrochemical Composites (Adv. Mater. 24/2020). Issue 24 (16th June 2020) - McCuskey, Samantha R.; Su, Yude; Leifert, Dirk; Moreland, Alex S.; Bazan, Guillermo C.
Abstract : Combining Shewanella oneidensis MR‐1 with the self‐doped conjugated polyelectrolyte CPE‐K leads to conductive networks that allow transfer of extracellular electron equivalents to an external gold electrode. In article 1908178, Guillermo C. Bazan and co‐workers show that 3D living biocomposites incorporating electrogenic bacteria and conductive gels can efficiently harvest biocurrent and provide a strategy to reduce barriers to charge extraction and injection in bioelectrochemical devices.